Architecture Of The Normative-Legal Information System, Methodological Provision Of Educational And Methodological Work Of The Institution Of Higher Education. - M.F. Pichugin; I.M. Sashchuk; O.O. Pisarchuk; M.Y. Rakushev; S.V. Kovbasyuk; M.A. Gornin; D.L. Fedorchuk (Kherson State University, 2009)
Purpose, functions, structure, electronic documents base contents and main issues of hardware and software architecture of the normative-legal information system, educational and methodological work of the institution of higher education are developed.